Question 1: "x\\frac{dy}{dx}-(x+1)y=xy^2"
Solution: Dividing equation by "-xy^2" :
"-y^{-2}y'+\\frac{x+1}xy^{-1}=-1"
Substituting "z=y^{1-2}=y^{-1}" , "\\frac{dz}{dx}=z'=-y^{-2}y'" , therefore: (1)
"z'+\\frac{x+1}{x}z=-1"
Substituting "z=uv" , "z'=u'v+uv'" : (2)
"u'v+uv'+\\frac{x+1}{x}uv=-1"
"u'v+u(v'+\\frac{x+1}{x}v)=-1" (3)
Setting the part inside () to 0 and separating variables:
"v'+\\frac{x+1}{x}v=0"
"\\frac{dv}{dx}=- \\frac{x+1}{x}v"
"\\int\\frac{dv}v = -\\int\\frac{x+1}{x}dx"
"ln(v)=-(x+ln(x)+ln(k))"
"v=e^{-(x+ln(x))}=\\frac1 {kxe^x}" (4)
Putting "v" from (4) into equation (3):
"\\frac1 {kxe^x}u'=-1"
"\\int du=-k\\int xe^x"
"u=-k(xe^x-e^x+e^x+C)=-k(e^x(x-1)+C)"
Finding z from (2):
"z=uv=\\frac{-(e^x(x-1)+C)}{xe^x}"
Finding y from (1):
"y=z^{-1}=-\\frac{xe^x}{e^x(x-1)+C}"
Answer 1: "y=-\\frac{xe^x}{e^x(x-1)+C}"
Question 2: "x^2y'-2xy=4y^4" , "y(1)=\\frac 12"
Solution: Dividing equation by "-\\frac1 3 x^2 y^4" :
"-3y^{-4}y'+\\frac 6 x y^{-3}=-\\frac {12} {x^2}"
Substituting "z=y^{-3}" , "z'=-3y^{-4}y'", therefore: (1)
"z'+\\frac6xz=-\\frac{12}{x^2}"
Substituting "z=uv , z'=u'v+uv'" : (2)
"u'v+uv'+\\frac6xuv=-\\frac{12}{x^2}"
"u'v+u(v'+\\frac6xv)=-\\frac{12}{x^2}" (3)
Setting the part inside () to 0 and separating variables:
"v'+\\frac6xv=0" (4)
"v'=-\\frac6xv"
"\\int \\frac {dv} v = -6 \\int \\frac {dx} x"
"ln(v)= -6 ln(x)-ln(k)=ln(kx^{-6})"
"v=\\frac 1 {kx^6}"
Putting "v" from (4) into equation (3):
"\\frac 1 {kx^6}u'=-\\frac{12}{x^2}"
"\\int du = \\int -12kx^4dx"
"u= k(-\\frac {12x^5}5+C)"
Finding z from (2):
"z=uv=-(\\frac {12x^5}5+C)*\\frac1{x^6}"
Finding y from (1):
"y=\\sqrt[3]{\\frac{5x^6}{12x^5+5C}}"
Assuming "y(1)=\\frac 12" : "\\sqrt[3]{\\frac{5*(1)^6}{12*(1)^5+5C}}=\\frac12"
"\\sqrt[3]{\\frac{5}{12+5C}}=\\frac12"
"\\frac{5}{12+5C}=\\frac18"
"C=\\frac{52}5"
Substitute C into general solution:
"y=\\sqrt[3]{\\frac{5x^6}{12x^5+52}}"
Answer 2: "y=\\sqrt[3]{\\frac{5x^6}{12x^5+52}}"
Comments
Leave a comment